Urgensi Penguatan Keterampilan Berpikir Kritis pada Mata Pelajaran Qur’an Hadist - M. Fahrurrozi (JURNAL PENELITIAN KEISLAMAN, 2021)
This research is in the form of a literature review on the urgency of strengthening critical thinking skills in the subject of the Qur'an hadith. Critical thinking is very necessary for someone, because in responding to and facing global challenges today, critical thinking skills are needed in order to solve the problems at hand. As for the benefits of a Muslim thinking critically of the Al-Qur'an and Hadith, namely: (1) a Muslim can capture the food and wisdom behind Allah SWT's creation, (2) increase confidence in the truth of Islam, (3) be able to answer all accusations which is not true of Islam from the haters of Islam, (4) increasing ghiroh in carrying out and avoiding Allah SWT's orders, (5) preventing someone from getting lost in interpreting the verses of Allah SWT, and (6) increasing gratitude for all the gifts of Allah SWT.